Skinnytaste simple : easy, healthy recipes using 7 ingredients or fewer - Homolka, Gina; Jones, Heather K. (Clarkson Potter/Publishers, 2023)
"#1 New York Times-bestselling author Gina Homolka returns with her easiest, simplest recipes yet--120 healthy dishes that use seven ingredients (or fewer!) to deliver big flavor without the fuss. Gina Homolka understands how tough it can be to put a meal together after a busy day or when she's tight for time. Skinnytaste Simple is the solution: recipes with minimum ingredients but maximum flavor and nutrition. These game-changing, no-fuss dishes use no more than seven ingredients each, which means healthy meals on the table faster, easier, and with more savings. From hearty breakfasts like Chilaquiles with Fried Eggs and PBJ Smoothie Bowls to crowd-pleasing dinners including One Pan Shrimp and Saffron Orzo and Caramelized Onion Fig Pizza, you'll find recipes the whole family will love. Plus, sweet indulgences are a snap with quick-and-easy chocolatey Flourless Sea Salt Brownies and make-ahead Strawberry and Cheese Turnovers. With Skinnytaste Simple, cooking delicious, nutritious meals for your family is easier than ever!"--